Physical, mechanical and energy characterization of wood pellets obtained from three common tropical species - Carrillo Parra, Artemio; Ngangyo Heya, Maginot; Colín Urieta, Serafín; Foroughbakhch Pournavab, Rahim; Rutiaga Quiñones, José Guadalupe; Correa Méndez, Fermín (2018)
ABSTRACT Background. The need for energy sources with low greenhouse gas emissions and sustainableproductionencouragesthesearchforalternativebiomasssources.However, the use of biomass fuels faces the problem of storage, transport and lower energy densities.Low-densityvaluescannegativelyaffectenergydensity,leadingtoanincrease intransportationandstoragecosts.Useofpelletsasalternativebiomasssourceisaway toreducethevolumeofbiomassbydensification,whichimprovestheirenergyquality. They are produced by diverse biomass resources and mainly from wood materials. In allcases,itisimportanttoevaluatethefuelcharacteristics,todeterminetheirsuitability on the heating system and handling properties. Methods. The present study determines and compares data from proximate analysis, calorific values, physical and mechanical properties of wood pellets produced from the common tropical species Acaciawrightii, Ebenopsisebano and Havardiapallens. Data were obtained from pellets produced from each species chips collected from an experimentalplantationandanalyzedthroughANOVAandKruskal–Wallistestat0.05 significance level. Results.Theresultsofdiameter,lengthandlength/diameterratiodidn’tshowstatistical differences (p > 0.05) among species. Acaciawrightii showed the highest density (1.2 g/cm3). Values on weight retained and compression test showed statistical differences(p=0.05)amongspecies.Havardiapallenswasmoreresistanttocompression strength than A.wrightii and Ebenopsisebano. Statistical differences (p<0.01) were alsoobservedforthevolatilematterandcalorificvalue.E.ebanohasthelowestvolatile matter (72%), highest calorific value (19.6 MJ/kg) as well as the fixed carbon (21%). Discussion.Thepelletsofthespeciesstudiedhaveahighenergydensity,whichmakes themsuitableforbothcommercialandindustrialheatingapplications.Apelletwithlow compression resistance tends to disintegrate easily, due to moisture adsorption. The percentages obtained for the resistance index were higher than 97.5%, showing that the pellets studied are high-quality biofuels. Proximate analysis values also indicate good combustion parameters. Pellets ofAcaciawrightii and Ebenopsisebano are the morefavorablerawmaterialsourcesforenergypurposesbecauseoftheirhighdensity, calorific value, low ash content and they also met majority of the international quality parameters.